KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) DALAM PELAKSANAAN PROGRAM HIBAH AIR MINUM DI KABUPATEN HULU SUNGAI UTARA - Sugianor Sugianor; Arief Budiman (stiatabalong.ac.id, 2018)
The main objective of this research is to describe in full the Performance of Regional Water Supply Companies (PDAMs) in the implementation of the Program Drinking Water Grant. How productivity, service quality, responsiveness, responsiveness and accountability have been implemented. And what factors influence the implementation of the Grant Program. This study uses a qualitative approach with descriptive-qualitative type. Which is where the sampling technique uses purposive sampling with a sample of 10 people. Data collection techniques used are observation, interviews and documentation studies. After the data is collected, then it is analyzed with techniques including data reduction, data presentation, and verification or drawing conclusions. The results of the study show that the performance of the Regional Water Supply Company (PDAM) in the implementation of the Water Hibah Program in Hulu Sungai Utara District is not entirely good, because there are still some indicators that have not been fulfilled such as in terms of productivity, service quality, and responsiveness, while what is fulfilled is in terms of responsibility and accountability. Although there are still deficiencies, the program continues to run and there are still many people who want to get it. In addition, there are several factors related to the implementation of this drinking water grant program, namely the absence of direct socialization to the community, slow incentive payments, potential customers not in place, many public complaints and changing installation standards. Keywords: performance; Hibah Program